Pengaruh Gaya Kepemimpinan, Lingkungan Kerja Non Fisik, dan Disiplin Kerja Terhadap Kinerja Pegawai Satuan Polisi Pamong Praja Kabupaten Malang (Studi Kasus Pada Pegawai Satpol PP Kabupaten Malang Bidang Trantribum Seksi Pengamanan) - Putri Ayu Maghfiro; Pardiman Pardiman; Sulton Sholehuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study was to determine the effect of leadership style, non-physical work environment and work discipline on the performance of Civil Service Police Unit employees in Malang Regency. This type of research is quantitative. The approach used in this study is an associative approach, using a saturated sample. Data collection techniques in this study using a questionnaire technique. Data analysis techniques in this study used the Classical Assumption Test, Multiple Regression, Hypothesis Test (t test and F test), and the Coefficient of Determination. Data processing in this study used the software program SPSS (Statistics Package for the Social Sciences) version 25. The results showed that it was partially known that leadership style had a positive and significant influence on the performance of Civil Service Police Unit employees in Malang Regency. Partially it is known that the non-physical work environment has a positive and significant influence on the performance of civil service police unit employees in Malang Regency. Partially it is known that work discipline has a positive and significant influence on the performance of Civil Service Police Unit employees in Malang Regency. Simultaneously it is known that leadership style, non-physical work environment, and work discipline have a significant positive influence on the performance of civil service police unit employees in Malang Regency. Keywords: Leadership Style, Non-Work Work Environment, Work Discipline, Employee Performance